2010
DOI: 10.1177/156482651003100302
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Locally Produced Foods and Potential for Developing Age-Appropriate Complementary Foods for Children under 2 Years of Age in Mali

Abstract: Locally produced indigenous foods in rural Mali were used to develop energy- and nutrient-dense complementary foods for children. Further research is needed to test the short- and long-term effects of consuming these dishes on the nutritional status of children 6 to 23 months of age in Mali.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Considering that in Zambia, and across sub-Saharan Africa, milled groundnut powder is often blended with cereals for making porridge (Ag Ayoya et al 2010;Hayes et al 1994;Onofiok and Nnanyelugo 1998), or added to leafy green vegetable preparations-locally called 'nsinjiro' (Oniang'o et al 2003), or used as an ingredient for complementary food for AIDS patients (Allison and Wilson 2011), the incidence of aflatoxins in milled groundnut powder is of public health interest. Specifically, early exposure to aflatoxin could exacerbate the incidence of stunting among children, which is estimated to affect 48% of children in Zambia (Moss et al 2002) and to compromise the health of AIDS patients by further depressing immunity and negatively affecting nutritional status (Fink-Gremmels 2008; Gong et al 2008;Jiang et al 2008;Jolly et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that in Zambia, and across sub-Saharan Africa, milled groundnut powder is often blended with cereals for making porridge (Ag Ayoya et al 2010;Hayes et al 1994;Onofiok and Nnanyelugo 1998), or added to leafy green vegetable preparations-locally called 'nsinjiro' (Oniang'o et al 2003), or used as an ingredient for complementary food for AIDS patients (Allison and Wilson 2011), the incidence of aflatoxins in milled groundnut powder is of public health interest. Specifically, early exposure to aflatoxin could exacerbate the incidence of stunting among children, which is estimated to affect 48% of children in Zambia (Moss et al 2002) and to compromise the health of AIDS patients by further depressing immunity and negatively affecting nutritional status (Fink-Gremmels 2008; Gong et al 2008;Jiang et al 2008;Jolly et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed development of the recipes was not given. A study in Mali showed that using local foods was more likely to be acceptable, affordable, feasible, and sustainable, because these foods were culturally appropriate and consumed on a daily basis (37). Preparing the recommended recipes should require little time and be affordable, so that mothers are willing to use the recipes during and after the study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, dried composite flours of cereals and legumes served as porridge to infants are currently promoted as complementary food in Sub‐Saharan Africa (Mensa‐Wilmot et al . 2001; Ayoya et al . 2010; Elemo et al .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest appropriate serum retinol levels that would support the growth demands for vitamin A were not met by giving these improved foods unless fortified with vitamin and mineral premix. Despite this, dried composite flours of cereals and legumes served as porridge to infants are currently promoted as complementary food in Sub-Saharan Africa (Mensa-Wilmot et al 2001;Ayoya et al 2010;Elemo et al 2011).…”
Section: Introductionmentioning
confidence: 99%